2004
DOI: 10.2307/3762087
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Gene Sequences Delimit Botryosphaeria australis sp. nov. from B. lutea

Abstract: Botryosphaeria lutea (anamorph Fusicoccum luteum) most easily is distinguished from other Botryosphaeria spp. by a yellow pigment that is formed in young cultures. This fungus has been reported from a number of cultivated hosts in New Zealand and Portugal. During a survey of Botryosphaeria fungi that occur on native Acacia species in Australia, a yellow pigment was observed in some cultures. These isolates were morphologically similar to B. lutea, but the pigment differed slightly from the one formed by authen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 33 publications
2
42
1
Order By: Relevance
“…The similarities between N. australe and N. luteum observed in this study were also reported by Slippers et al (2004a) and Amponsah et al (2011), who also reported great variation between N. parvum isolates, since colony pigmentation on PDA plates was pale yellow, cream or white. However, the morphological characteristics did allow grouping of many isolates in presumptive species which were confirmed with ARDRA, and DNA sequencing of rDNA in this study.…”
Section: Discussionsupporting
confidence: 84%
“…The similarities between N. australe and N. luteum observed in this study were also reported by Slippers et al (2004a) and Amponsah et al (2011), who also reported great variation between N. parvum isolates, since colony pigmentation on PDA plates was pale yellow, cream or white. However, the morphological characteristics did allow grouping of many isolates in presumptive species which were confirmed with ARDRA, and DNA sequencing of rDNA in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Note the central hole (arrow). Bars: 3, 5-9,12=10 µm; 1, 2, 4, 10, 11, 13,14=5 µm yellow pigment in culture (Slippers et al 2004) that was not observed in our strains. In addition, the overlapping of conidial size within this genus (Slippers and Wingfield 2007) compels us to be cautious before considering the presence of Neofusicoccum australe in Argentina.…”
Section: Remarks On Fungal Speciescontrasting
confidence: 68%
“…Ascospores, although rarely observed, were hyaline, aseptate, fusoid to ovoid. The second group was characterised by the production of a yellow pigment after two to three days on PDA, a defining characteristic of both N. australe and N. luteum (Witcher and Clayton 1963, Pennycook and Samuels 1985, Slippers et al 2004b, with later abundant white fluffy aerial mycelia. The culture eventually turned dark grey to black.…”
Section: Morphological Characterisationmentioning
confidence: 99%